MAKSIMALISASI KEUNTUNGAN PRODUKSI AIR TAHU AYAK DENGAN PEMROGRAMAN LINEAR MELALUI METODE GRAFIK DAN PERANGKAT LUNAK POM-QM - adinda Rinato (MATHunesa: Jurnal Ilmiah Matematika, 2026)
Tofu water and tofu pudding are traditional Chinese culinary dishes originating from Palembang. In this city, they are locally referred to as "Tau Hu Hue" and "Tau Hu Cui," terms derived from the Teochew dialect, which is predominantly spoken by the residents of Palembang. This study examines a small-medium enterprise named Air Tahu Ayak, situated on Jalan W.R. Supratman. The business offers two primary products: tofu water and tofu pudding. The main objective of this research is to maximize the profit of the Air Tahu Ayak enterprise by employing the graphical method of linear programming and utilizing POM-QM software. The linear programming graphical technique is a method for resolving linear optimization problems through graphical visualization. This approach is particularly suitable for scenarios involving two decision variables, as they can be plotted on a Cartesian coordinate plane. The study incorporates information technology, specifically the POM-QM tool, to determine the highest possible profit. The analysis reveals that implementing the graphical method with POM-QM software yields a maximum profit of Rp734,000, achieved by selling 220 portions of tofu pudding (X1) and 110 portions of tofu water (X2).